Microbiological Analysis and Content of Heavy Metals in Different Candies, Chocolates, and Their Wrappers in Bangladesh - Kazi Milenur Rahman Prattay; Md. Tanvir Ahmed Chowdhury; Md. Raihan Sarkar; Tanvir Rahman; Sharmin Zaman Emon; Abrar Hossain; Hredoy Ghosh Rajib; Md. Abdurrahim (International Journal of Food Science)
Present study investigates 39 brands of candies, chocolate, and litchis, purchased from Dhaka City, Bangladesh, for their moisture content, sulphated ash value, heavy metal, and bacterial contamination. All the brands showed moisture content (0.64%-4.775%) within the BSTI range, but sulphated ash values (18.80%-25.72%) were beyond the accepted value. Pb, Cd, Ni, and Cr ranged from 0.24-2.40 μg/g, 0.071-0.44 μg/g, 0.38-48.10 μg/g, and 0.50-12.79 μg/g, respectively, in the tested brands. Most of the brands contained Pb and Cd beyond the acceptable limits of WHO/FDA. Pb (2.24-2586.75 μg/g) was found in high concentration in the packaging of most brands, and Ni and Cd ranged from 2.10-108.05 μg/g and 1.68-45 μg/g, respectively. Bacterial presence was found in 15 brands, and 4 of them had a total aerobic bacterial count of >1 log CFU/g. Consumption of such contaminated confectionaries holds significant public health risks, specially in children, and demands necessary precautionary steps.